Ultrastructural studies of bovine paratuberculosis (Johne's Disease) (Mongolian Journal of Agricultural Sciences, 2015)
In the present study, we report the ultrastructural morphologic features of infected macrophages, epithelioid cells, Langhans' giant cells and a more detailed impression of the interaction between macrophages and engulfed bacteria in ileum and mesenteric lymph nodes of cows naturally infected with Mycobacterium avium subsp. paratuberculosis (MAP).Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 61-65